Fieldwork, Serendipity, and Ethiopian Women - Molvaer, Reidulf K. (Aethiopica, 2007)
Anthropologists are increasingly using sociological methods in fieldwork; but when doing research in cultures other than their own, this will often impoverish their investigation, as they do not know the most revealing questions to ask. By keeping an open mind, surprising information may unexpectedly turn up. This is, e.g., the case when investigating the situation of women, where it may be necessary to conduct studies in indirect ways, in combination with more factual statistical data collection. ATTENTION: Due to copy-right no online publication is provided.